The Influence of Rental Price on Rental Volume in Gunawangsa Apartement: Pengaruh Harga Sewa Terhadap Volume Penyewaan Pada Apartemen Gunawangsa - Nuryadi; Kurniawati; A’yuna, Qori; Setyowati, Lis; Farida, Nur (Procedia of Social Sciences and Humanities, 2022)
The research aims to find out how the effect of the rental price on the rental volume in the Gunawangsa Apartment. The data examined is in the form of the Gunawangsa Apartment occupancy report for the period 2019 to 2020. The method that researchers use is quantitative method using secondary data. The data analysis used is a simple linear regression analysis using one independent variable namely the rental price and one dependent variable namely the rental volume. Data collection techniques using documentary techniques. The results of this study indicate that there is a significant effect between the rental price on the rental volume but has a negative linier pattern. the results of a simple linier regression analysis with Y = 87.627 – 5.38000000X showing a negative linear pattern, meaning that lower rental prices can increase rental volume and vice versa.